JOB INSECURITY, FEAR OF LITIGATION, AND QUALITY OF WORK LIFE ASSOCIATED WITH JOB DISSATISFACTION AMONG EXPATRIATE NURSES IN GULF COUNTRIES - YOUSAF , B; ALEEM , S (Biological and Clinical Sciences Research Journal, 2024)
Job satisfaction is crucial for maintaining the well-being and productivity of nurses, particularly expatriate nurses working in Gulf countries. Factors such as job insecurity, fear of litigation, and quality of work life (QWL) significantly impact job satisfaction, yet little is known about their interplay among Pakistani expatriate nurses. Objective: To assess the associations between job insecurity, fear of litigation, QWL, and job dissatisfaction among Pakistani nurses working in Gulf countries. Methods: A descriptive cross-sectional study was conducted among 103 nurses. Data were collected using a structured questionnaire, and descriptive and inferential statistics were analyzed using SPSS version 26. Key variables included job insecurity, fear of litigation, QWL, and job dissatisfaction. Results: Job insecurity and QWL had mean scores of 3.32 and 3.38, respectively, indicating moderate levels. Fear of litigation scored lower with a mean of 2.30. Job dissatisfaction had a mean score of 2.57, reflecting moderate dissatisfaction. Correlations among variables revealed significant associations between job insecurity, QWL, and job dissatisfaction. Conclusion: Job insecurity and QWL are significant determinants of job dissatisfaction among expatriate nurses. Addressing these factors through policy reforms, professional development programs, and supportive work environments is essential to improve nurse retention and healthcare quality in Gulf countries.